TRANSLANGUAGING AS STRATEGY IN IMPROVING INTERACTIONS IN EFL CLASS AMONG PRIMARY SCHOOL STUDENTS AND TEACHER IN SD N 5 KAMPUNG BARU - Rika Fitri Darmawan; Ni Wayan Surya Mahayanti; Luh Gd Rahayu Budiarta (Journal Informatic, Education and Management (JIEM), 2026)
This study aimed to investigate the implementation of a translanguaging strategy to improve classroom interaction in English learning. It also explored students’ and teacher’s perceptions of the strategy and the challenges encountered during its implementation. This study employed Classroom Action Research (CAR) conducted in two cycles consisting of planning, acting, observing, and reflecting stages. The participants were students in a junior high school English classroom. Data were collected through classroom observations, questionnaires, interviews, and a teacher’s diary. The data were analyzed to examine changes in classroom interaction and participants’ perceptions of translanguaging. The findings revealed that translanguaging improved classroom interaction throughout the research cycles, with the overall classroom interaction score reaching 83.58%, indicating a high level of interaction. Students became more confident and actively participated in classroom communication. Both students and the teacher expressed positive perceptions of translanguaging, reporting that it facilitated lesson comprehension and encouraged participation. However, challenges remained in balancing the use of Indonesian and English during classroom interaction. Overall, translanguaging proved to be an effective strategy for enhancing classroom interaction in English learning.